Chemical characterization of the antioxidant and α-glucosidase inhibitory active fraction of Malus transitoria leaves. (30th August 2022) - Lu, Yongchang; Wang, Xin; Wu, Yong; Wang, Zeyu; Zhou, Na; Li, Jinjie; Shang, Xiaoya; Lin, Pengcheng
Highlights: The antioxidant and α -glucosidase inhibitory effects of M. transitoria and the optimal extraction method were determined. Guided by in vitro bioassays and UPLC-Orbitrap-MS/MS analysis, the most active fraction in M. transoria was determined. From the strong active fraction, 81 compounds were identified, of which 2 were novel and 79 were first-time discoveries. Abstract: Chinese Tibetan tea made from the tender leaves of Malus transitoria is a widely consumed health drink, but there are few reports on its chemical composition and biological activity. In this study, we found that a 50% ethanol extract of M. transitoria had good antioxidant and α -glucosidase inhibitory activities in vitro . Guided by in vitro bioassays, chromatographic separation and purification were conducted, and the most active fraction in M. transitoria was determined. UPLC-Orbitrap-MS/MS was used to further quickly and comprehensively characterize the chemical composition. Library searches, MS/MS fragmentation patterns of two isolated reference compounds, and bibliography were used to annotate 81 compounds, of which 2 were new compounds, and 79 were identified from M. transitoria for the first time. This study provides a scientific basis for the development of antioxidant and anti-diabetic functional foods from M. transitoria .